2016
DOI: 10.1007/s13187-016-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians’ Knowledge, Attitudes, and Practices Toward Colorectal Cancer Screening

Abstract: The purpose of this study was to assess family physicians' knowledge, attitudes, and practices toward colorectal cancer (CRC) screening. The population in this cross-sectional study consisted of 290 family physicians working in Samsun, Turkey, contacted between 15 June and 15 July 2015 and agreeing to participate. A questionnaire prepared by the authors on the basis of the relevant literature was applied at face-to-face interviews. The first part of the questionnaire inquired into sociodemographic information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
11
1
1
Order By: Relevance
“…A FOBT screening recommendation from a family physician/GP is the most influential factor in a patient's participation in CRC screening (Cole et al, 2002;Zajac et al, 2010). Yet, variation in practitioner screening knowledge and attitude appears to influence their CRC screening practice (Perin et al, 2015;Dawson et al, 2017;Şahin and Aker, 2017), although Australian studies pre-date the NBCSP implementation (Youl et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…A FOBT screening recommendation from a family physician/GP is the most influential factor in a patient's participation in CRC screening (Cole et al, 2002;Zajac et al, 2010). Yet, variation in practitioner screening knowledge and attitude appears to influence their CRC screening practice (Perin et al, 2015;Dawson et al, 2017;Şahin and Aker, 2017), although Australian studies pre-date the NBCSP implementation (Youl et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…In France, for example, which also has a population-based FIT screening programme, individuals who receive an invitation to screen need to request the FIT from their GP. 9 In countries with opportunistic screening programs (like the US, 10 Italy, 11 and Turkey), 12 the initiative to screen may lie entirely in the hands of the GP or the individual.…”
Section: Introductionmentioning
confidence: 99%
“…It is internationally well-documented that physicians' attitudes, recommendations, and behaviour may influence their patients’ decisions to participate in CRC screening and having follow-up after a positive FIT result. 7,9,12,1822 For instance, it has been reported that GPs can increase screening participation among their patients: providing GPs with a list of non-adhering patients contributes to slightly higher rates of uptake of FIT, 20 GP involvement instead of hospital involvement can increase CRC screening participation, 11 and a GP-endorsed reminder letter is more effective than a standard reminder letter in increasing uptake in CRC screening. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The two studies demonstrated that most physicians were aware of methods of CRC screening, but have low belief in the effect of screening on CRC occurrence, confusion about how methods of screening are performed, and insufficient information concerning the ages and frequency of screening. [ 13 14 ] Similar data specific to the primary health care community in KSA is lacking.…”
Section: Introductionmentioning
confidence: 99%